FORMATION OF DIGITAL COMPETENCIES WITHIN THE FRAMEWORK OF THE “DIGITAL CHAIR” PROGRAM - Elena G. Agapova (Russian Journal of Education and Psychology)
Background. In the artificial intelligence age, it is not only IT graduates who have digital competencies, but also schoolchildren. Improvement of skills to work in the digital environment and with digital products is necessary in all spheres of life. The national project “Digital Chair” is aimed at solving this problem, i.e. formation and mastering of modern digital competences.